Sanaaq: roman - Nappaaluk, Mitiarjuk (Stanké, 1969)
« Sanaaq est le nom de l'héroine, dont on suit, tout au long du récit, les heurs et malheurs, avant et après l'arrivée des premiers Blancs en pays inuit. À l'image de Mitiarjuk, c'est une femme forte et équilibrée, sensible et déterminée, qui nous fait découvrir de l'intérieur, comme aucun Occidental, fût-il anthropologue, n'a encore pu le faire, la vie et la psychologie des Inuits confrontés à une nature extrême, à la nécessité du partage et à l'envahissement de leur territoire par les Blancs et leur civilisation. » – Résumé de Publications Nunavik.
Section: 303 p. ; 21 cm.
Keywords: 1900-1999; 1930-1939; 1940-1949; amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; littérature; littérature inuit; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires

The Homosexual Role - McIntosh, Mary (Social Problems, 1968)
The current conceptualization of homosexuality as a condition is a false one, resulting from ethnocentric bias. Homosexuality should be seen rather as a social role. Anthropological evidence shows that the role does not exist in all societies, and where it does it is not always the same as in modern western societies. Historical evidence shows that the role did not emerge in England until towards the end of the seventeenth century. Evidence from the "Kinsey Reports" shows that, in spite of the existence of the role in our society, much homosexual behavior occurs outside the recognized role and the polarization between the heterosexual man and the homosexual man is far from complete.
Keywords: 1900-1999; 1960-1969; LGBTQIA2+; cours; discipline; homosexualité; premier cycle; périodes historiques; santé; sciences humaines; sexualité; soc2014; sociologie; thématiques